2006
DOI: 10.1111/j.1399-3046.2006.00569.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and management of patients with propionic acidemia undergoing liver transplantation: A comprehensive review

Abstract: Propionic acidemia is a rare metabolic disorder that often results in episodic hyperammonemia, basal ganglia infarction, mental retardation, and cardiomyopathy. OLT has been used as a treatment for propionic acidemia, but its benefit in patients with this disease is unclear. The current study was undertaken to clarify the role of OLT in the management of this disease. The medical literature, a national registry of US OLT recipients, and a single institution liver transplant experience were reviewed for cases o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 26 publications
2
68
0
1
Order By: Relevance
“…Despite these, when LT is successful, we and others (11,(14)(15)(16) have shown that the quality of life of the surviving patients is transformed. Acute metabolic decompensations are abolished, with a follow-up up to 21 years.…”
Section: Discussionmentioning
confidence: 94%
“…Despite these, when LT is successful, we and others (11,(14)(15)(16) have shown that the quality of life of the surviving patients is transformed. Acute metabolic decompensations are abolished, with a follow-up up to 21 years.…”
Section: Discussionmentioning
confidence: 94%
“…OLT for PA was first attempted in a 26-month child in 1992 in Birmingham, UK, but he died in the early postoperative period. Following this there were 10 reported cases of OLT for PA but only with partial success (15). The overall mortality rate following OLT was 36% (4/11).…”
Section: Discussionmentioning
confidence: 97%
“…Some clinics recommend avoidance of high protein foods but not a specifi c protein restriction [ 24 ]. In other cases, medical food may need to be continued if protein tolerance is less than the DRI.…”
Section: Transplantationmentioning
confidence: 99%